Colorectal Polyp Evaluation Management and Its Role in Gastrointestinal Tract Malignancy - Didi Kurniadhi; Ari Fahrial Syam; Chudahman Manan; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Colorectal polyp is one of important factors that have roles in developing malignancy of lower gastrointestinal tract. Adenomatous polyp is the most common colorectal polyps and it has been known as a lesion precursor for transformation process in developing gastrointestinal malignancy. Such transformation is known as adenocarcinoma sequence, a long-term process which usually does not elaborate any symptoms and remains asymptomatic. Since most colorectal polyps are asymptomatic, they are usually undiscovered at the time of diagnosis and results to the increasing case of malignancy especially the colorectal cancer. Considering that colorectal cancer still becomes one of the most common causes of death and morbidity worldwide, early detection and elimination of colorectal polyp may have a significant role in preventing lower gastrointestinal tract malignancy. Keywords: polyp, colorectal polyp, adenomatous polyp